Effects of end‐stage renal disease and dialysis modalities on blood ammonia level. Issue 3 (1st November 2016) - Vaziri, Nosratola D.; Khazaeli, Mahyar; Nunes, Ane C. F.; Harley, Kevin T.; Said, Hyder; Alipour, Omeed; Lau, Wei Ling; Pahl, Madeleine V.
Abstract: Introduction: Uremia results in a characteristic breath odor (uremic fetor) which is largely due to its high ammonia content. Earlier studies have shown a strong correlation between breath ammonia and blood urea levels and a 10‐fold reduction in breath ammonia after hemodialysis in patients with chronic kidney disease. Potential sources of breath ammonia include: (i) local ammonia production from hydrolysis of urea in the oropharyngeal and respiratory tracts by bacterial flora, and (ii) release of circulating blood ammonia by the lungs. While the effects of uremia and hemodialysis on breath ammonia are well known their effects on blood ammonia are unknown and were explored here. Methods: Blood samples were obtained from 23 hemodialysis patients (immediately before and after dialysis), 14 peritoneal dialysis patients, and 10 healthy controls. Blood levels of ammonia, creatinine, urea, and electrolytes were measured. Findings: No significant difference was found in baseline blood ammonia between hemodialysis, peritoneal dialysis and control groups. Hemodialysis procedure led to a significant reduction in urea concentration (P < 0.001) which was paradoxically accompanied by a modest but significant (P < 0.05) rise in blood ammonia level in 10 of the 23 patients studied. Change in blood ammonia pre‐ and post‐hemodialysis correlated with change in serum bicarbonate levels (r = 0.61, P < 0.01). On subgroup analysis of patients who had a rise in blood ammonia levels after dialysis, there was a strong correlation with drop in mean arterial pressure (r = 0.88, P < 0.01). The nadir intradialytic systolic blood pressure trended lower in the hemodialysis patients who had a rise in blood ammonia compared to the patients who manifested a fall in blood ammonia (124± 8 vs. 136± 6 mmHg respectively, P = 0.27). Discussion: Fall in blood urea following hemodialysis in ESRD patients was paradoxically accompanied by a modest rise in blood ammonia levels in 43% of the patients studied, contrasting prior reported effects of hemodialysis on breath ammonia. In this subgroup of patients, changes in blood ammonia during hemodialysis correlated with rise in blood bicarbonate and fall in mean arterial blood pressure.